ANALISA PENGARUH LAMA FERMENTASI DAN TEMPERATUR DISTILASI TERHADAP SIFAT FISIK (SPECIFIC GRAVITY DAN NILAI KALOR) BIOETANOL BERBAHAN BAKU NANAS (ANANAS COMOSUS) - Sutanto, Rudy; Jaya, Harisman; Mulyanto, Arif (Dinamika Teknik Mesin: Jurnal Keilmuan dan Terapan Teknik Mesin, 2013)
Indonesia is one of the countries which has a largest pineaple plantation in Asia, that is more than 165.690 hektare besides Thailand, Filipina, and Malaysia. Pineaple is one of the plants which contains karbohidrat and sugar as well as corn, cassava, sugar palm, etc. Thus in this occasion the pineaple will be used as material for producing bioetanol cause besides its quantity is large, it’s potential to make bioetanol.            This research head for identify the efect of fermentation periode and distilation  temperature as independent variable to the specific gravity and heating value as dependent variable. In this research the fermentation periode used are 5, 7, and 9 days while distilation temperature are 60, 75, and 800C. Producing of this pineaple bioetanol is doing by fermentation proses. In producing this pineaple bioetanol each sample which mass is 1750 gr added with 75 gr crushed yeast or equal with 4,3 % mass of sample.              From the research it’s found that the alcohol content is increase with fermentation periode and decresing of distilation temperature. Specific gravity decrease with increasing of fermentation periode and decreasing of distilation temperature. Heating value is increase with increasing of fermentation periode and deacreasing of distilation temperature.